The domestic dimension of cross-border governance: Patterns of coordination and cooperation - Chilla, Tobias (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
Contemporary debates in border studies tend to see the national level as a rather residual category. There are, however, strong arguments that the national level still plays an important role for the governance of border regions. The question is what kind of formats are in place related to coordination and networking of border regions within national settings. The aim of this paper is to provide an exploratory typology of domestic governance settings. The underlying empirical study shows a large diversity of governance patterns in thirteen European countries. A synthetic typology reveals five approaches, namely centralist, decentral and selective coordination as well as transnational and laisser-faire approaches. On this basis, the explanatory factors of the revealed governance patterns are discussed. The state structure (federal, centralist) plays an important role. Moreover, contingent political strategies, embedded in political culture and path dependency, help to understand the differences and the similarities between the analysed countries. The domestic governance dimension seems to bridge the frictions between the rather classical inner-state hierarchies and the soft networking tools of cross-border governance in the strict sense.